Intravenous administration of flecainide or propafenone in patients with recent-onset atrial fibrillation does not predict adverse effects during 'pill-in-the-pocket' treatment. Issue 7 (29th March 2010) - Alboni, Paolo; Botto, Giovanni L; Boriani, Giuseppe; Russo, Giovanni; Pacchioni, Federico; Iori, Matteo; Pasanisi, Giovanni; Mancini, Marina; Mariconti, Barbara; Capucci, Alessandro
Abstract : Background: Pill-in-the-pocket treatment should be prescribed only if the administration of a loading oral dose of flecainide or propafenone has been proved safe in hospital, since major adverse effects have been reported in 5% of patients during in-hospital treatment. However, in emergency rooms, the oral administration of these drugs for the conversion of atrial fibrillation (AF) is very rarely used because it is time consuming. Objective: To investigate whether tolerance to intravenous administration of flecainide or propafenone might predict the safety of pill-in-the-pocket treatment—the out-of-hospital self-administration of these drugs after the onset of palpitations—in patients with AF of recent onset. Methods: One hundred and twenty-two patients with AF of recent onset who were successfully treated (conversion of AF within 2 h without major adverse effects) in hospital with intravenous flecainide or propafenone were discharged on pill-in-the-pocket treatment. Results: During a mean follow-up of 11±4 months, 79 patients self-treated 213 arrhythmic episodes; treatment was successful in 201 episodes (94%). Major adverse events occurred in five patients (6%) and in four (5%) of these during the first oral treatment (one syncope, two presyncope, one sinus arrest). No patient reported symptoms attributable to bradyarrhythmia or hypotension during the self-treatment of arrhythmic recurrences when the first oral treatment was not accompanied by any major adverse effects. The study was prematurely terminated because of the high incidence of major adverse effects during the first out-of-hospital treatment. Conclusion: The patient's tolerance of intravenous administration of flecainide or propafenone does not seem to predict adverse effects during out-of-hospital self-administration of these drugs.